Social Change in the Gulf Region Multidisciplinary Perspectives - Rahman, Md Mizanur; Al-Azm, Amr (Gulf Studies, 2023)
This open access book, comprising thirty-nine chapters divided into social, cultural, economic, and political spheres, offers a unique opportunity to dive into the complex, dynamic, and sometimes contradictory transformation of Gulf societies in the last few decades. Whilst the Gulf region has at times been seen as impervious to this natural phenomenon of transformation-timeless, never changing, deeply rooted in its ancient tribal customs and traditions and able to blend past and present seamlessly without suffering the wrenching trauma of change-this is clearly not the case, and the region is not immune to the inevitable forces of social change. There is no doubt today that the social change sweeping the Gulf has been profound, affecting almost every aspect of life in the Gulf societies. This volume has an encyclopedic value as the chapters collectively offer multifaceted and multidisciplinary perspectives to understand social change in the Gulf region. Through these chapters, the role of economic and educational transformation, and the impact of social media, migration, and urbanization have in driving social change in the Gulf societies is examined in detail with a focus on their directions, magnitudes, and relevant policy options. It also considers how COVID-19 is affecting the lives of the people in the Gulf. This book bridges gaps in the understanding of the rapid pace of social change in the Gulf, offering practical solutions for policy interventions. It is of interest to scholars and students in Middle Eastern studies, specifically, as well as sociology, media studies, migration studies, and educational policy. ; This book focuses on the role of economic transformation, education, social media, migration, and urbanization in engaging social change in the Gulf societies, with a focus on their directions, magnitudes, and relevant policy options. It also takes into account how COVID-19 is affecting the lives of the people in the Gulf. Over the last few decades, the Gulf countries have undergone profound social change - generally understood as changes in human interactions and relationships that transform cultural and social institutions - affecting almost every aspect of life in GCC societies. The volume considers how the Gulf countries have achieved success in the education sector, and also examine the changes in conservative attitudes towards female education, as the enrolment of women in higher education is increasing steadily across the Gulf. It also unpacks the social impact of technology, as satellite television and the Internet have dramatically expanded exposure to outside views. Access to social media has similarly proved a powerful force for social transformation. The Gulf states now account for the world's largest flow of South-South migration, and the growth of the non-national population, as well as rapid urbanization, have also had a profound impact on Gulf society. This volume thus attempts to bridge gaps in understanding the rapid social change in the Gulf, offering practical solutions for policy interventions. It is of interest to scholars and students in Middle Eastern studies, specifically, as well as sociology, media studies, migration studies and educational policy.